Spectrophotometric Estimation of Ranolazine in Tablet Dosage Form - VETRICHELVI, S.; ARUNA, AJITHADAS; NIRAIMATHI, V.; JERAD SURESH, A. (Asian Journal of Chemistry, 2010)
Two new, simple sensitive and reproducible spectrophotometric methods have been developed for the estimation of ranolazine in tablet dosage form, (method A and method B). Method A is based on the formation of a yellow coloured chromogen with ferric chloride and it obeys Beer's law in concentration ranging from 100-800 μg/mL and exhibiting maximum absorption at 379 nm. Method B is difference spectroscopic method which is based on shifting the λmax by changing the pH of the solution by adding 1 M HCl and 1 M NaOH. At 215 nm the difference in absorbance is noted and it obeys Beer's law in concentration ranging from 10-60 μg/mL. The methods were extended to tablet formulation and there was no interference from excipients and diluents. These methods have been statistically validated and are found to be precise and accurate.